Longitudinal naming and repetition relates to AD pathology and burden in autopsy‐confirmed primary progressive aphasia. Issue 1 (2nd August 2021) - Cousins, Katheryn A.Q.; Bove, Jessica; Giannini, Lucia A. A.; Kinney, Nikolas G.; Balgenorth, Yvonne R.; Rascovsky, Katya; Lee, Edward B.; Trojanowski, John Q.; Grossman, Murray; Irwin, David J.
Abstract: Introduction: In primary progressive aphasia (PPA) patients with autopsy‐confirmed Alzheimer's disease (AD) or frontotemporal lobar degeneration (FLTD), we tested how the core clinical features of logopenic PPA—naming and repetition—change over time and relate to pathologic burden. Methods: In PPA with AD (n = 13) or FTLD (n = 16) pathology, Boston Naming Test and Forward Digit Span measured longitudinal naming and repetition; as reference, Mini‐Mental State Examination (MMSE) measured global cognition. Pathologic burden in left peri‐Sylvian regions was related to longitudinal cognitive decline. Results: PPA with AD showed greater decline in naming ( P  = 0.021) and repetition ( P  = 0.020), compared to FTLD; there was no difference in MMSE decline ( P  = 0.99). Across all PPA, declining naming ( P  = 0.0084) and repetition ( P  = 0.011) were associated with angular, superior‐middle temporal (naming P  = 0.014; repetition P  = 0.011) and middle frontal (naming P  = 0.041; repetition P  = 0.030) pathologic burden. Discussion: Unique longitudinal profiles of naming and repetition performance in PPA with AD are related to left peri‐Sylvian pathology.